2008
DOI: 10.1002/lt.21380
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation and characterization of a novel population of progenitor cells from unmanipulated rat liver

Abstract: Widespread use of liver transplantation in the treatment of hepatic diseases is restricted by the limited availability of donated organs. One potential solution to this problem would be isolation and propagation of liver progenitor cells or stem cells. Here, we report on the isolation of a novel progenitor cell population from unmanipulated (that is, no prior exposure to chemicals and no injury) adult rat liver. Rat liver cells were cultured following a protocol developed in our laboratory to generate a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
(78 reference statements)
0
35
0
Order By: Relevance
“…However, it remained unclear whether such cells are present in normal adult liver. Cell lines with HSC characteristics have been established from normal mouse (Fougere-Deschatrette et al, 2006), human (Herrera et al, 2006) and rat (Sahin et al, 2008) liver. However, these cell lines were derived from a hepatocyte-enriched cell population by centrifugation using a Percoll gradient or from unfractionated cells, leaving their origin ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remained unclear whether such cells are present in normal adult liver. Cell lines with HSC characteristics have been established from normal mouse (Fougere-Deschatrette et al, 2006), human (Herrera et al, 2006) and rat (Sahin et al, 2008) liver. However, these cell lines were derived from a hepatocyte-enriched cell population by centrifugation using a Percoll gradient or from unfractionated cells, leaving their origin ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Because most liver disorders result from hepatocyte dysfunction, HTx has attracted considerable attention [25,34]. HTx could alleviate the donor organ shortage if it was useful as a bridging therapy to OLTx [5,6,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical application of the University of Wisconsin (UW) solution in the late 1980s considerably improved the quality and tolerance of grafts to cold ischemia [25]. Perfluorocarbon (PFC) liquids have been investigated as a medical application for many years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But progress is hampered by difficulties in maintaining and expanding postnatal hepatic stem/progenitor cells and a lack of specific surface markers. Few studies reported successes in isolating hepatic progenitor cells from normal postnatal liver, which have been differently characterized by several markers, including CD34 [7,8], CD44 [9], c-kit [7,10], Thy-1 [7,11], CD133 [12,13], sca-1 [14], and side population cell attributes [15]. It suggests that these candidates of stem/progenitor cells in normal postnatal liver may represent different tissue-specific cell populations, because of various isolation protocols and different culture systems used.…”
Section: Introductionmentioning
confidence: 99%